The Relations between Reactivity at 4 Months and Behavioral Inhibition in the Second Year: Replication across Three Independent Samples. (4th November 2014) - Fox, Nathan A.; Snidman, Nancy; Haas, Sara A.; Degnan, Kathryn A.; Kagan, Jerome
<x xml:space="preserve">Abstract</x> This paper examines the predictive relations between two infant temperamental biases assessed at 4 months and inhibited behavior during the first 2 years of life in three independent samples from two research laboratories. Although each sample used slightly different criteria for classifying infants, the results across samples were consistent. Infants of both genders who displayed high levels of motor activity and distress to unfamiliar events were more inhibited at 14 months of age. By 24 months, there were significant sex differences: Boys identified as high reactive were more inhibited than high reactive girls.